PENGEMBANGAN STANDAR KOMPETENSI GURU DI SD NEGERI 1 BAMBAN BARITO TIMUR KALIMANTAN TENGAH - Desti Desti (Jurnal Pendidikan dan Pengajaran, 2023)
The purpose of this research is to see the extent of teacher professionalism in education at SD Negeri Bamban, Central Kalimantan. The research method uses the interview method as qualitative research by transcribing the recording into factual solids, then coding, then creating themes through the entire interview transcript. The results of this study show that teacher professionalism in SD Negeri Bamban is still visible through personal competence, professionalism in teaching, and social competence.